1984
DOI: 10.1135/cccc19840039
|View full text |Cite
|
Sign up to set email alerts
|

Contribution to the thermodynamics of complexes of alkali metal cations with dibenzo-18-crown-6 in water-nitrobenzene extraction system

Abstract: The stability constants for the ML+ complex species, where M+ is an alkali metal cation and L is dibenzo-18-crown-6, in nitrobenzene saturated with water were calculated by employing published equilibrium data. The stability is found to increase in the cation order Li+ < Cs+ < Rb+ < K+ < Na+. For the NaL+, KL+, RbL+, and CsL+ complex cations the individual extraction constants in the water-nitrobenzene system were determined; their values increase in the series Na+ < K+ < Rb+ < Cs+.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
0

Year Published

1992
1992
2016
2016

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 145 publications
(29 citation statements)
references
References 0 publications
1
28
0
Order By: Relevance
“…From the results of our previous papers [20,21], it follows that the two-phase water-Pb(NO 3 ) 2 -nitrobenzene-1 (cyclosporin A)-Sr(DCC) 2 extraction system (see ''Experimental'' section), chosen for determination of the stability constant of the cationic complex 1ÁPb 2? in nitrobenzene saturated with water, can be characterized by the main chemical equilibrium…”
Section: Extraction Experimentsmentioning
confidence: 99%
“…From the results of our previous papers [20,21], it follows that the two-phase water-Pb(NO 3 ) 2 -nitrobenzene-1 (cyclosporin A)-Sr(DCC) 2 extraction system (see ''Experimental'' section), chosen for determination of the stability constant of the cationic complex 1ÁPb 2? in nitrobenzene saturated with water, can be characterized by the main chemical equilibrium…”
Section: Extraction Experimentsmentioning
confidence: 99%
“…Previous results [5,[12][13][14][15][16] indicated that the two-phase waterHCl/nitrobenzene-NaDCC-1 (beauvericin) extraction system (see ''Experimental''), chosen for determination of the stability constant of the cationic complex 1ÁH 3 O ? in nitrobenzene saturated with water, can be characterized by the main chemical equilibrium (Eq.…”
Section: Extraction Experimentsmentioning
confidence: 99%
“…Furthermore (referring to [31,[54][55][56]), for the exchange extraction constants K ex (HL ? , Cs ? )…”
Section: Extraction Experimentsmentioning
confidence: 99%
“…= 0.4. Previous results [31,[54][55][56] indicated that the two-phase water-HL ? Cl -/nitrobenzene-CsDCC-1 (HAB-based receptor) extraction system (see ''Experimental''), which was chosen to determine the stability constant of the cationic complex 1ÁHL ?…”
Section: Extraction Experimentsmentioning
confidence: 99%